Early period maladaptive schemas, psycological symptoms and examining the tendency of deception - Güler, Kahraman (The European Research Journal, 2022)
Objectives: There are relationships between early maladaptive schemas, psychological symptoms, and deception structures. Researches have not examined all these structures collectively in a single study. The aim of this study is to investigate the relationship between early maladaptive schemas, psychological symptoms and deception tendency according to various sociodemographic features. This research also aims to contribute to clinical studies. Many counselees who receive psychotherapy have problems in their relationships. Therefore, it is important to understand what is causing these problems. Methods: The research was carried out with a total of 407 non-clinical participants, 200 women and 207 men who aged between 18 and 45 live in Istanbul. Data were collected from the participants using the Sociodemographic Information Form, the Young Schema Scale, the Brief Symptom Inventory, and the Deception Tendency Scale. Results: According to the results of the applied correlation analyzes, it was found that there was a significant positive correlation between the components of early maladaptive schemas, psychological symptoms and infidelity tendency. The findings were interpreted and discussed within the framework of the literature. Conclusions: An effective treatment plan can be developed that specifically addresses the etiological factor for problems that arise in close relationships. There is no significant positive relationship between the brief symptom inventory and the deception tendency scale. The base of this weak relationship is most likely to be associated with The Brief Symptom Inventory sub-dimensions of depression, anxiety, negative self, somatization, and hostility. We propose a research design to predict the relationship between EMS, personality, personality disorders, and the tendency of deception for other studies.